Calidad del agua de la planta de tratamiento de Ayapamba y posible impacto en la salud gastrointestinal de la población. - Ruiz Arias, Justin Alfredo (My University, 2025)
This research aims to evaluate the quality of the treated water at the Ayapamba plant, located in the province of El Oro, Ecuador, and its possible impact on the gastrointestinal health of the local population. The study was developed for four months, including the dry and rainy season, through sampling at three points of the system: capture (raw water), plant exit and home network (tap water). Physicochemical analyses of pH, turbidity, hardness, sulfates, phosphates, nitrites and arsenic were performed, in accordance with INEN 1108:2020 and the guidelines of the World Health Organization (WHO). In addition, microbiological parameters such as fecal coliforms and Escherichia coli, indicators of biological contamination, were evaluated. The results indicated that most of the physicochemical parameters were kept within the regulatory limits. However, high levels of phosphates were recorded in raw water, possibly due to agricultural runoff or decomposition of organic matter, the presence of fecal coliforms was also evidenced, mainly during the rainy season, which could be due to problems in the water disinfection process, infiltrations or formation of biofilms in the network. Simultaneously, surveys were applied to 191 inhabitants, observing a statistically significant association (p < 0.05) between the consumption of water directly from the distribution network and the appearance of gastrointestinal diseases such as diarrhea, vomiting and abdominal pain. It is concluded that, although the treatment system meets the standards in general terms, some deficiencies were identified such as the presence of fecal coliforms and variations in certain physicochemical parameters, especially in the rainy season, in which this can compromise the health of the population. It is recommended to strengthen quality control, improve plant operation and promote safe consumption practices in the community.
La presente investigación tiene como objetivo evaluar la calidad del agua tratada en la planta de Ayapamba, ubicada en la provincia de El Oro, Ecuador, y su posible impacto en la salud gastrointestinal de la población local. El estudio se desarrolló durante cuatro meses, incluyendo la época seca y lluviosa, mediante un muestreo en tres puntos del sistema: captación (agua cruda), salida de planta y red domiciliaria (agua de grifo). Se realizaron análisis fisicoquímicos de pH, turbidez, dureza, sulfatos, fosfatos, nitritos y arsénico, conforme a la norma INEN 1108:2020 y las directrices de la Organización Mundial de la Salud (OMS). Además, se evaluaron parámetros microbiológicos como coliformes fecales y Escherichia coli, indicadores de contaminación biológica. Los resultados indicaron que la mayoría de los parámetros fisicoquímicos se mantuvieron dentro de los límites normativos. No obstante, se registraron niveles elevados de fosfatos en el agua cruda, posiblemente por escorrentía agrícola o descomposición de materia orgánica, igualmente se evidenció presencia de coliformes fecales, principalmente durante la época lluviosa, lo cual podría deberse a problemas en el proceso de desinfección del agua, infiltraciones o formación de biofilms en la red. Simultáneamente, se aplicaron encuestas a 191 habitantes, observándose una asociación estadísticamente significativa (p < 0.05) entre el consumo de agua directamente de la red distribución y la aparición de enfermedades gastrointestinales como diarrea, vómitos y dolor abdominal. Se concluye que, aunque el sistema de tratamiento cumple con los estándares en términos generales, se identificaron algunas deficiencias como presencia de coliformes fecales y variaciones en ciertos parámetros fisicoquímicos, especialmente en la época lluviosa, en la cual esto puede comprometer la salud de la población. Se recomienda fortalecer el control de calidad, mejorar la operación de la planta y promover prácticas seguras de consumo en la comunidad.
Keywords: CALIDAD DEL AGUA; SALUD GASTROINTESTINAL; AGUA POTABLE; ARSÉNICO